2019
DOI: 10.1115/1.4044238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fuel Composition on Gas Turbine Engine Performance

Abstract: An industrial gas turbine can run on a wide variety of fuels to produce power. Depending on the fuel composition and resulting properties, specifically the hydrogen–carbon ratio, the available output power, operability, and emissions of the engine can vary significantly. This study is an examination of how different fuels can affect the output characteristics of Solar Turbines Incorporated industrial engines and highlights the benefits of using fuels with higher hydrogen–carbon ratios including higher power, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…The corresponding H/C values of the naphtha fraction are identical (1.93) in both analytical methods. Although the fact that the naphtha fraction of a fossil origin has the H/C value higher than a diesel fraction of the same origin, that is not in the case when these fractions come from plastic pyrolysis oils [66,67]. Furthermore, the oxygen elemental composition determined by EA is higher in comparison with the obtained results of GC × GC-FID in both studied samples.…”
Section: Elemental Analysiscontrasting
confidence: 53%
“…The corresponding H/C values of the naphtha fraction are identical (1.93) in both analytical methods. Although the fact that the naphtha fraction of a fossil origin has the H/C value higher than a diesel fraction of the same origin, that is not in the case when these fractions come from plastic pyrolysis oils [66,67]. Furthermore, the oxygen elemental composition determined by EA is higher in comparison with the obtained results of GC × GC-FID in both studied samples.…”
Section: Elemental Analysiscontrasting
confidence: 53%
“…In particular, the benefits of biodiesel as an alternative aviation fuel have attracted research interest in addressing the inefficient performance of conventional fossil fuels [10]. The incomplete combustion of fossil fuel hydrocarbons adversely impacts GTE performance in terms of the GHG emission levels, fuel consumption, engine running cost [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Burnes and Camou [25] studied the effect of fuel composition on the performance of a gas turbine engine, and how different fuel types (natural gas and crude oil) affect the output characteristics of power turbine engines and highlighted the benefits of using fuel that contains high percentages of Hydrogen and carbon, including higher energy, higher more effectiveness and reduced carbon emissions, as well as the problems of the combustion process that must be taken into account such as self-ignition, reflux, explosion, and combustion instability, which become more obvious when changing hydrogen and carbon, and the researchers concluded that increasing the proportion of H2 in fuel results more efficient H2 combustion effects ,while Low H/C fuels lower ignition temperature are typical, and the results showed that natural gas is better than fossil fuels in this study.…”
Section: The Effect Of Temperatures Type Of Fuel and Type Of Filters ...mentioning
confidence: 99%